Value of diffusion-weighted images in diagnosis of locoregionally recurrent rectal tumors. Issue 3 (August 2021) - Javadrashid, R.; Mahmoudpour, M.; Akhavi Milani, A.; Jalili, J.; Hajalioghli, P.; Nezami, N.
Abstract: Introduction: To assess the value of referring to Diffusion-weighted images in evaluation of T2-weighted images of patients clinically suspicious of locoregional rectal cancer recurrence. Methods: After ethics committee approval and informed consent were obtained, 37 consecutive patients (male/female of 22/15; mean age 56 ± 13.5 SD) clinically suspicious of recurrent rectal tumor were prospectively included in the study over a two-year period. T2-weighted images of the patients were reviewed and the results were recorded. Right after that, the corresponding DWI images were provided for the radiologist and new ratings were given to the patients after taking into account the DWI findings. Finally, the patients underwent tissue biopsy. Receiver Operating Characteristic (ROC) analysis was performed, and Area Under the Curve (AUC) of the "T2-weighted alone" and "T2-weighted + DWI" methods were calculated and compared. Results: "T2-weighted alone" and "T2-weighted + DWI" methods had an AUC of 0.64 (95% CI 0.47 to 0.79) and 0.75 (95% CI 0.58 to 0.88), respectively. The Difference between the two AUCs was 0.11 (P = 0.16). In the subgroup of patients having equivocal ratings in T2-weighted images, DWI images correctly identified 81% (13/16) of patients with true tumor recurrence and 66% (8/12) of patients without recurrence. Conclusion: Our results suggest that referring to DWI does not significantly change the overall diagnostic performance of T2-weighted images. However, DWI is of great value in evaluation of the subgroup of patients with equivocal findings in T2-weighted images. Studies with larger sample sizes are needed to confirm these findings. Implications for practice: When T2-weighted images are equivocal, DWI images may be helpful in evaluation of patients with suspected locoregional recurrence of rectal tumor.